Metal‐Oxide‐Free Methylammonium Lead Iodide Perovskite‐Based Solar Cells: the Influence of Organic Charge Transport Layers. Issue 15 (12th June 2014) - Malinkiewicz, Olga; Roldán‐Carmona, Cristina; Soriano, Alejandra; Bandiello, Enrico; Camacho, Luis; Nazeeruddin, Mohammad Khaja; Bolink, Henk J.
<x xml:space="preserve">Abstract</x> Metal‐oxide‐free methylammonium lead iodide perovskite‐based solar cells are prepared using a dual‐source thermal evaporation method. This method leads to high quality reproducible films with large crystal domain sizes allowing for an in depth study of the effect of perovskite film thickness and the nature of the electron and hole blocking layers on the device performance. The power conversion efficiency increases from 4.7% for a device with only an organic electron blocking layer to almost 15% when an organic hole blocking layer is also employed. In addition to the in depth study on small area cells, larger area cells (approx. 1 cm−2) are prepared and exhibit efficiencies in excess of 10%.